PETA KENDALI ATRIBUT UNTUK MENGIDENTIFIKASI KECACATAN PRODUK FURNITURE DI PT. ISI - Yunitasari, Elly Wuryaningtyas; Royanto, Puji (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2020)
PT. ISI is one of the furniture industries in Bantul area. In that area there are a lot of advanced furniture industries. To compete with similar company, we need a perfect product quality to gain the trust of consumer. Thus good quality control effort is needed by PT. ISI to be able to compete and continue to grow. The problems from this research that is what type of defective product that occur and how the quality of the final product at PT. ISI. The steps in this research are first collecting defect product data, calculating Center Line (CL), Upper Control Limit (UCL) and Lower Control Limit (LCL) and then identifying cause and effect of defects using a fishbone diagram. There are five types of defects in the production process of PT ISI, the five types of defects are broken or cracked, the color is not appropriate, scratch, impact former and lamination. The implementation of the final product quality control at PT ISI is still within the control limit, this can be seen in the control chart graph which shows no deviation that occur from the upper control limit and the lower control limit.